ВПЛИВ ЄМНОСТІ КОНДЕНСАТОРА РОЗРЯДНОГО КОЛА НАПІВПРОВІДНИКОВИХ ЕЛЕКТРОРОЗРЯДНИХ УСТАНОВОК НА ЇХНІ ВИХІДНІ СТРУМИ ОБМЕЖЕНОЇ ТРИВАЛОСТІ - Щерба, А.А.; Супруновська, Н.І.; Ломко, М.О. (Інститут електродинаміки Національної академії наук України, 2021)
Based on the analysis of transient processes of oscillatory and aperiodic discharges of the storage capacitor of the electric discharge installation to the load, it is proved that an increase in its capacity always causes an increase in the value of the discharge current corresponding to a fixed duration of the discharge, less than the duration of reaching the maximum value of the discharge current. For the capacities of the discharge capacitor varied over a wide range, the change in the value of the discharge current in the load during its forced interruption at a certain time was studied. Based on this study, we proposed a method for increasing the rate of rising of impulse currents in the load, which consists in choosing a discharge capacitor with a larger capacity compared with a capacity sufficient to implement the desired technological mode, and forced interrupting the current in the load at a certain point in time, which corresponds to a certain fixed duration discharge (less than the duration of reaching the maximum value of the discharge current when the capacitor capacity is sufficient to implement the required technological mode). The forced limitation of the discharge duration is carried out by a fully controlled semiconductor switch. This method can be used as the basis for the production of spark erosion nano-sized powders of metals and alloys. Ref. 15, fig. 3, table .